Perceptions of medical students towards and effectiveness of online surgical curriculum: a systematic review - Shye-Jao Wu (BMC, 2021)
Abstract Background Online education has been used as an adjunct modality for teaching and it attracts attention in recent years as many medical students can not accomplish their clerkship in the hospital due to COVID-19 pandemic. This study aims to collect the articles related to online surgical education for medical students, and to analyze the effectiveness of online education and the perceptions of the medical students. Method We performed a systemic literature search in PubMed, MEDLINE, EMBASE, ERIC and Cochrane library. Keywords used for searching included “medical student”, “online education”, “online teaching”, “online learning”, “distance learning”, “electronic learning”, “virtual learning” and “surgical”. Medical education research study quality instrument (MERSQI) was used for the evaluation of the quality of the searched articles. Results From 1240 studies retrieved from the databases, 13 articles were included in this study after screening. The publication year was from 2007 to 2021. The mean MERSQI score of the 13 searched articles was 12.5 +/− 1.7 (range 10.0-14.5). There were totally 2023 medical students who attended online surgical curriculum. By online course, improvement of understanding and knowledge on the studied topics could be reached. The confidence in patient encounters could be improved by online curriculum with sharing experiences, discussing, and role playing. However, students felt concentration was poor during online course. Medical students studying through video platform could get better test scores than those studying with textbooks. Regarding basic surgical skills, online teaching of suturing and knot-tying could be possible and was appreciated by the students who could practice away from the hospital and get feedbacks by instructors through online environment. The scores for the clinical competence assessment for incision, suturing and knot-tying were found to be no significant difference between the online teaching group and face-to-face teaching group. Conclusion Online surgical curriculum for medical students is not easy but inevitable in the era of COVID-19 pandemic. Although online course is not the same as physical course, there are some efforts which could be tried to increase the effectiveness. Basic surgical skills could also be taught effectively through online platform. Even if the COVID-19 pandemic is over in the future, online curriculum could still be a helpful adjunct for surgical education.